Analysis Of The Influence Of Leadershiip Style, Work Motivation, And Organizational Culture On The Work Discipline Of Village Officials At The Muliorejo Village Office, Sunggal Subdistrict, Deli Serdang Regency - Vira Febriani; Teguh Wahyono; Hasrul Azwar Hasibuan (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This research aims to analyze the influence of leadership style, work motivation, and organizational culture on the work discipline of village officials at the Muliorejo Village Office, Sunggal District, Deli Serdang Regency, both partially and simultaneously. The population consists of 30 respondents with a saturated/sensus sampling technique, meaning the entire population is used as the research sample. The research was conducted in 2025, using questionnaires to obtain primary quantitative data, which was then analyzed with SPSS 26 using multiple linear regression. The analysis shows that leadership style, work motivation, and organizational culture individually and together have a significant positive influence on work discipline. The partial test (t-test) revealed: leadership style (t-count 2.412 > t-table 2.05 with sig. 0.029); work motivation (2.789 > t-table 2.05 with sig. 0.015); organizational culture (2.544 > t-table 2.05 with sig. 0.027). The simultaneous test (F-test) yielded F-count 12.644 (sig. 0.004), with F-table 2.98, thus all hypotheses (H1-H4) are accepted. Organizational culture is the dominant factor with the highest beta (0.542), explaining 42.9% of the variation in work discipline, with a fairly strong correlation (R = 0.530).